Suspected ST segment elevation myocardial infarction referred for primary angioplasty: a masquerader - Yennu Nandan, Abhivrath (BMJ Case Rep, 2019)
A 50-year-old man collapsed at the roadside with retrosternal pain, shortness of breath and generalised weakness. An ECG in the emergency department was reported as demonstrating ST segment elevation of up to 1.5 mm in leads V1 to V3, leading to a diagnosis of an acute ST-elevation myocardial infarction. He was immediately transferred to the cardiac catheterisation laboratory. Introduction of a coronary catheter produced signs that raised suspicion of aortic dissection. An aortogram revealed a grossly dilated aortic root of 7.3 cm with a type A ascending aortic dissection. The patient was urgently transferred to the cardiothoracic surgical centre and underwent emergency aortic root and ascending aorta replacement. Following a 20-day hospital admission, and postoperative atrial fibrillation, the patient made a steady and full recovery.